Transitioning to Adulthood under Duress: The Experience of Young Offenders in Quebec’s Juvenile Justice System - Dumollard, Marie (Swiss Journal of Sociocultural Anthropology, 2020)
This article examines the support provided by Quebec’s juvenile justice system for young people classified as offenders who transition to adulthood and who are in open custody. Analyzing life-course narratives of these young people, it highlights the paradoxical nature of penal interventions that, vacillating between support and control, simultaneously enable and constrain the development of autonomy. Faced with restrictive and contradictory institutional regulations, young people adapt their relationship to socio-judicial services by adopting three types of attitude.